Enhancement of Antigen Presentation by Deletion of Viral Immune Evasion Genes Prevents Lethal Cytomegalovirus Disease in Minor Histocompatibility Antigen-Mismatched Hematopoietic Cell Transplantation - Gezinir, Emin; Podlech, Jürgen; Gergely, Kerstin M.; Becker, Sara; Reddehase, Matthias J.; Lemmermann, Niels A. W. (Frontiers in Cellular and Infection Microbiology, 2020)
Hematoablative treatment followed by hematopoietic cell transplantation (HCT) for reconstituting the co-ablated immune system is a therapeutic option to cure aggressive forms of hematopoietic malignancies. In cases of family donors or unrelated donors, immunogenetic mismatches in major histocompatibility complex (MHC) and/or minor histocompatibility (minor-H) loci are unavoidable and bear a risk of graft-versus-host reaction and disease (GvHR/D). Transient immunodeficiency inherent to the HCT protocol favors a productive reactivation of latent cytomegalovirus (CMV) that can result in multiple-organ CMV disease. In addition, there exists evidence from a mouse model of MHC class-I-mismatched GvH-HCT to propose that mismatches interfere with an efficient reconstitution of antiviral immunity. Here we used a mouse model of MHC-matched HCT with C57BL/6 donors and MHC-congenic BALB.B recipients that only differ in polymorphic autosomal background genes, including minor-H loci coding for minor-H antigens (minor-HAg). Minor-HAg mismatch is found to promote lethal CMV disease in absence of a detectable GvH response to an immunodominant minor-HAg, the H60 locus-encoded antigenic peptide LYL8. Lethality of infection correlates with inefficient reconstitution of viral epitope-specific CD8+ T cells. Notably, lethality is prevented and control of cytopathogenic infection is restored when viral antigen presentation is enhanced by deletion of immune evasion genes from the infecting virus. We hypothesize that any kind of mismatch in GvH-HCT can induce ‘non-cognate transplantation tolerance’ that dampens not only a mismatch-specific GvH response, which is beneficial, but adversely affects also responses to mismatch-unrelated antigens, such as CMV antigens in the specific case, with the consequence of lethal CMV disease.